Examining The Protection Of Access To And Delivery Of Healthcare By The National Health Act 2014* - Akpoghome, Theresa U (Advances in Social Sciences Research Journal, 2018)
Nigeria Health care delivery has been on the decline for decades with no remedy in sight until 2014 when Nigeria enacted the National Health Act which is the first legislation to comprehensively address the issues of health care in the country. In view of this, the paper examines the protection of access to and delivery of health care by the National Health Act of 2014. To achieve this, the paper discusses the challenges to access to health care prior to the enactment of the Act in order to appreciate the enormity of what has been and be able to identify the extent to which the Act has addressed the existing trend. The paper discusses the provisions of the Act and observes that the Act is a laudable piece of legislation which tries to address the status quo in the health sector. Despite the objective of the Act which is to provide a framework for standards and regulation of health services, the paper notes that some parts of the Act needs to be reviewed especially the issue of organ removal and transplant in emergency situation without the consent of the donor. The paper also finds that the Act did not specify what constitutes the basic minimum package of health services but left it for the Minister of Health to determine. The paper notes that this is a dangerous trend as Nigerians may never know what they are entitled to. The paper finally notes that the Act is unpopular as many Nigerians are not aware of its existence or what it provides. The paper therefore calls for the urgent implementation of the Act by putting mechanisms in place towards creating the needed awareness to help Nigerians take the benefit provided by the Act as this will help Nigeria to attain Universal Health Coverage and the Sustainable Development Goals with respect to health.